Economic damages of cassava brown streak disease in sub-Saharan Africa: a framework - Manyong, Victor M.; Maeda, C.; Kanju, E.; Legg, James P. (International Society for Tropical Root Crops, 2012)
Cassava brown streak disease (CBSD) remains a major threat to the livelihoods of millions of smallholders in sub-Saharan Africa. This viral disease was initially confined to the coastal lowland areas of eastern and southern Africa. More recently there has been a major new outbreak in the Great Lakes region of eastern and central Africa, and two virus species have been shown to cause the disease. This paper describes a framework that could be used to make a meaningful assessment of economic damages of CBSD. The model is then applied to the current situation of sub-Saharan Africa (SSA) using secondary data collected from various studies on cassava-growing areas of SSA. The virus causing CBSD generates two broad categories of damages: quantitative and qualitative. The variables associated with the quantitative damage include: total abandonment of roots with a severity score of 3 and above, reduction in yield due to disturbances in the physiology of the plant and through early harvesting to escape total crop failure, and by additional labor required to process damaged fresh roots. On the qualitative side, roots affected by the virus experience changes in their chemical content (e.g. lower starch content or provitamin A), which result in lower nutritional or industrial quality of the produce. Such products attract lower prices in the markets compared to healthy products, or are rejected altogether. Farmers can use thrown-away roots as livestock feed or to process into other products such as local alcohol. Such residual gains (if any) must be discounted when assessing the economic damages of CBSD. The main challenge in estimating the economic damage at a continental level remains the lack of data or insufficient data beyond those few from the experimental plots. Another bottleneck from research is to generate adequate information on the relationship between CBSD incidence and production loss. This relationship is all the more complex since CBSD has multiple symptom types, some or all of which may be present. The application of the above framework resulted in the identification of 6 countries where CBSD is confirmed and 2 countries where the disease is suspected out of the 39 countries that produce cassava in SSA. In the eight countries, about 1.6 million tons of fresh roots are lost annually due to CBSD, amounting to about US$75 million. The true economic losses are certainly much higher, since several of the types of losses highlighted in the framework have not been factored in due to lack of data and knowledge. In addition, recent survey data from the affected countries suggest that incidence of CBSD continues to increase. Accurate estimates of loss are vital in this dynamic situation. The challenge to both research and development institutions, therefore, is to assemble authoritative data on ALL the key components of CBSD damage in order to capture fully the economic consequences of this deadly disease in the continent.